Students Who Analyze Their Own Data in a Course-Based Undergraduate Research Experience (CURE) Show Gains in Scientific Identity and Emotional Ownership of Research† - Katelyn M. Cooper (American Society for Microbiology, 2020)
While it has been established that course-based undergraduate research experiences (CUREs) lead to student benefits, it is less clear what aspects of CUREs lead to such gains. In this study, we aimed to understand the effect of students analyzing their own data, compared with students analyzing data that had been collected by professional scientists. We compared the experiences of students in a CURE investigating whether the extinction risk status of terrestrial mammals and birds is associated with their ecological traits. Students in the CURE were randomly assigned to analyze either data that they had collected or data previously collected by professional scientists. All other aspects of the student experience were designed to be identical. We found that students who analyzed their own data showed significantly greater gains in scientific identity and emotional ownership than students who analyzed data collected by professional scientists.